Analyzing the influence of gastric intestinal metaplasia on gastric ulcer healing in Helicobacter pylori–infected patients without atrophic gastritis. Issue 1 (December 2017) - Chen, Li-Wei; Chang, Liang-Che; Hua, Chung-Ching; Hsieh, Bor-Jen; Chen, Shuo-Wei; Chien, Rong-Nan
Abstract Background Gastric epithelial hyper-proliferation was reported in patients withHelicobacter pylori (H. pylori )–infected gastric mucosa with intestinal metaplasia (IM) changes. In patients with gastric ulcer (GU) and IM, the GU may have a different healing rate in comparison to patients without IM. This study aimed to compare the difference in GU healing betweenH. pylori– infected patients with IM and those without IM. Methods We retrospectively analyzed patients at the Keelung Chung Gung Memorial Hospital during the period from March 2005 to January 2011. The inclusion criteria were: 1) endoscopic findings of GU and biopsy histological examination plus rapid urease test indicatingH. pylori infection; 2) gastric IM adjacent to a GU but with no atrophic gastritis changes; 3) patients receivingH. pylori eradication triple therapy and 8 weeks of maintenance therapy with a proton pump inhibitor; and 4) patients receiving follow-up endoscopy within the 3rd and the 4th months after treatment. Results In total, 327 patients with GU andH. pylori infection (136 with IM and 191 without IM) were included. Patients with IM had a higher GU healing rate than those without IM (91.9% vs. 84.3%, P = 0.040). Multivariate logistical regression analysis revealed that failure ofH. pylori eradication (Odds = 4.013, 95% CI: 1.840–8.951, P < 0.001) and gastric IM (Odds = 0.369, 95% CI: 0.168–0.812, P = 0.013) were the predictors of non-healing GU following treatment. Conclusions Patient with gastric IM change may have a higher GU healing rate than those without gastric IM. However, successfulH. pylori eradication is a more important factor for GU healing than gastric IM.